(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2007)
Objectives: The aim of the study was to evaluate the performance of the postgraduate students in Objective Structured Practical Examination (OSPE) in the speciality of Obstetrics and Gynaecology. This new trend of assessment was implemented first time in Bangladesh as a part of clinical assessment in the Fellowship examination. Materials and Methods: Three Mock OSPE were arranged for the postgraduate students before appearing in the final Fellowship examination by the faculty of Obstetrics and Gynaecology along with Bangladesh College of Physicians and Surgeons (BCPS) in the month of September and November 2005. A total of 109 students participated. In OSPE, students rotate through different stations where they are asked to perform certain tasks. In each circuit three different categories of stations were arranged, procedural stations for demonstrating certain skills, interactive stations with simulated patients for patient education, counselling and history taking and question stations where specimens, instruments, data and scenarios were placed for evaluation of interpretation, decision making and problem solving skills. For the procedural and interactive stations a preformed standardized checklist was placed with an observer for evaluation. For the question stations answer keys were prepared for checking. Pass mark was set at 52% (13 grade) as decided by the Examination Committee of BCPS. Results: Fifty six (51.38%) students scored 52% or above and declared as having passed. Performance in the procedural station was very poor in the first Mock (40.20% success rate) but the results got better in the subsequent Mock (52% in Mock II and 72% in Mock III). Performance in the interactive stations was not at all satisfactory, 75% could not achieve the desired credit revealing the fact that the students were very poor in communication skills. Performance in the question stations was variable depending upon the objective and task enrolled. Conclusions: OSPE is objective, structured, reliable and valid way to assess all the component of clinical competency and is an option to improve quality of clinical assessment, teaching and learning. (J Bangladesh Coll Phys Surg 2007; 25 : 3-8)